Staphylococcus aureus susceptibilities from wounds of patients who use illicit fentanyl - Drew T. Dickinson; Stephen Saw; Lauren Dutcher; Christina Maguire; Adrienne Terico; Margaret Lowenstein; Sonal Patel (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract